Pattern of adverse drug reactions reported at a tertiary care teaching hospital in northern India - Singh, Arpita; Jain, Atul; Soni, Maneesh; Shukla, Pooja; Lahon, Joonmoni; Verma, Ajay Kumar (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Adverse drug reactions (ADRs) are among the leading cause of morbidity and mortality in hospital setup. This study was conducted with the aim of understanding the pattern and occurrence of ADRs to minimize their risk and safeguard public health. Methods: This study is a retrospective analysis of pattern of ADRs reported at ADR monitoring centre (AMC) in a tertiary care hospital. A total of 207 spontaneous ADR reports collected over a period of 18 months were analysed for pattern and type of reactions, demographic profile of patients, organ system affected by ADRs, causative drugs, route of drug administration, severity of reaction, their outcome, management and causality assessment. Results: Most common age group affected by ADRs was 41-50 years with almost equal involvement of male and female gender. Cutaneous reactions involving skin like rashes and itching were most common ADRs. The most common causative drug for ADRs were antimicrobials agents like Penicillin and Cephalosporin group of antibiotics. Orally administered drugs were most commonly involved in causing ADRs. Most of the ADRs belonged to Type A category, were non-serious and moderate in severity. Most of the patients recovered from the ADRs on stopping the suspected drug. On assessing the causality, most of the ADRs were probable with the suspected drugs. Conclusions: Most of the patients recover from ADRs with appropriate and timely intervention, but it is important to understand the pattern and occurrence of ADRs for patient safety and this is possible only with an effective and robust pharmacovigilance system.